THE EFFECT OF RELIGIOUS MUSIC THERAPY ON REDUCING THE DEGREE OF MENSTRUAL PAIN IN ADOLESCENT GIRLS - Rahmat Kurniawan Rahmat; Dhia Dhia Diana Fitriani; Putri Putri Wulandari; Nurmiaty Nurmiaty; Saman (Journal of Health, Sport, and Nursing, 2025)
Introduction: Dysminorrhea is a complaint of menstrual pain that is often experienced by adolescent girls, affecting their daily activities. Non-pharmacological interventions such as religious music therapy can be an alternative in reducing menstrual pain. Purpose: To determine the effect of religious music therapy on reducing the degree of menstrual pain in adolescent girls. Method: This study used a quasi experiment design with a one group pretest-posttest design. The sample amounted to 15 adolescent girls in RT 09 Kp. Mekar Baru, Tangerang Regency, selected by purposive sampling. Pain measurement used NRS scale, and the data were analyzed by Wilcoxon test. Results: There was a decrease in the degree of menstrual pain after religious music therapy intervention. Wilcoxon test results showed a p value = 0.001 (p < 0.05), which means there is a significant effect of religious music therapy on reducing menstrual pain. Conclusion: Religious music therapy effectively reduces the degree of menstrual pain in adolescent girls. Suggestion: Young women are advised to use religious music therapy as a non-pharmacological independent method to reduce menstrual pain.